Feasibility Analysis of Presentation of Indonesian Language Textbooks Class VIII Curriculum 2013 Issued by the Ministry of Education and Culture 2017 - Pristi Dian Nova; Prida Asriani; Pitriyasari; Muhammad Mukhlis (UIR Press, 2022)
The purpose of this study is to describe the presentation techniques contained in the Indonesian language textbook class VIII Curriculum 2013 published by the Ministry of Education and Culture 2017. The method used is a qualitative method with point data analysis techniques. Class VIII Curriculum 2013 published by the Ministry of Education and Culture in 2017 whether it is feasible or not in terms of presentation feasibility. Through textbooks, students can do the exercises instructed in the textbook independently and think and be able to be constructive, able to make observations and do the exercises instructed in the textbook independently. The results of the analysis regarding the feasibility of presenting this book are almost in accordance with the provisions set by the National Education Standards Agency and the Center for Books (2014). The material presented is also not out of thinking ability for junior high school students because the material in the book is also presented in a simple way.